Advancing California's microgrid communities through anticipatory energy resilience - Aczel, Miriam R.; Peffer, Therese E. (Frontiers in Climate, 2023)
The impacts of a changing climate and related weather events on mental and physical health, quality of life, and economic and social well-being of communities disproportionately affect low income, geographically isolated, or otherwise marginalized populations. One promising solution to improve energy resilience and justice is implementation of community-based and -managed microgrids able to connect to the main grid and ‘island’ or stand-alone during energy emergencies—a shift in how energy is produced and transmitted from a centralized to a local system. Decentralized energy systems in California are currently regulated under a complex framework designed for centralized power generation and distribution. With the shift in design to decentralization, this paper discusses the benefit for inclusion of principles drawn from Anticipatory Regulation and Resilience Thinking in revising and enhancing regulatory frameworks. Key principles include: energy justice and equity, aim to implement local governance rather than centralized control, iterative processes with inclusive participation, eco-creation of solutions, and experimentation to develop resilient energy solutions in the face of uncertain future risks and technical innovations.